Emotive Meaning in Political Argumentation - Macagno, Fabrizio; Walton, Douglas (Informal Logic, 2019)
Donald Trump’s speeches and messages are characterized by terms that are commonly referred to as “thick” or “emotive,” meaning that they are characterized by a tendency to be used to generate emotive reactions. This paper investigates how emotive meaning is related to emotions, and how it is generated or manipulated. Emotive meaning is analyzed as an evaluative conclusion that results from inferences triggered by the use of a term, which can be represented and assessed using argumentation schemes. The evaluative inferences are regarded as part of the connotation of emotive words, which can be modified and stabilized by means of recontextualizations. The manipulative risks underlying the misuse and the redefinition of emotive words are accounted for in terms of presuppositions and implicit modifications of the interlocutors’ commitments.